From Learning to Performance: The Strategic Role of Knowledge Management in Indonesian Universities - Suci Putri Lestari; Vanessa Gaffar; Lili Adi Wibowo; Alfira Sofia (MASI Mandiri Edukasi, 2026)
Higher education institutions in developing countries face persistent challenges in enhancing institutional performance amid rapid digital transformation, yet the mechanisms through which organizational learning and knowledge management contribute to performance outcomes remain underexplored in the Indonesian context. This study aims to: (1) analyze the effect of the learning organization on knowledge management strategy; (2) examine the influence of knowledge management strategy on university performance; and (3) investigate the direct effect of the learning organization on university performance at universities in Eastern Priangan, Indonesia. A quantitative cross-sectional survey design was employed, involving 420 academic and administrative staff selected through purposive sampling. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with WarpPLS 7.0 software. The results demonstrate that the learning organization exerts a strong and significant positive effect on knowledge management strategy (β = 0.899, p < 0.001, R² = 0.807) and on university performance (β = 0.521, p < 0.001). Knowledge management strategy also significantly influences university performance (β = 0.412, p < 0.001), with the combined model explaining 75.6% of the variance in performance outcomes (R² = 0.756). These findings confirm that an organizational learning culture is a critical antecedent to the development of effective knowledge management systems, which, in turn, drive improvements in academic quality, research productivity, and institutional governance. This study enriches the learning organization literature in the Indonesian higher education context and provides practical implications for university leaders in designing sustainable institutional development strategies.